A case of varicella zoster virus meningitis following BNT162b2 mRNA COVID-19 vaccination in an immunocompetent patient. (December 2021) - Maruki, Taketomo; Ishikane, Masahiro; Suzuki, Tetsuya; Ujiie, Mugen; Katano, Harutaka; Ohmagari, Norio
Highlights: Varicella zoster virus meningitis post first dose of BNT162b2 mRNA COVID-19 vaccine A 71-year-old immunocompetent woman developed fever, headache and stiff neck Varicella zoster virus confirmed by polymerase chain reaction of cerebrospinal fluid This is the fourth such report worldwide suggesting a possible link to the vaccine Abstract: We report a case of varicella zoster virus (VZV) meningitis following BNT162b2 mRNA COVID-19 vaccination in an immunocompetent patient. A final diagnosis was made based on identification of VZV via positive polymerase chain reaction of cerebrospinal fluid along with characteristic symptoms such as fever, headache, and stiff neck. This phenomenon has been reported elsewhere; this is the 13th such case reported worldwide and the 7th case in immunocompetent patients, indicating the need for careful monitoring after COVID-19 vaccines.